2019
DOI: 10.3389/fphys.2019.01453
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Hypoxia and Programing of Lung Metabolism

Abstract: Gestational hypoxia is a risk factor in the development of pulmonary hypertension in the newborn and other sequela, however, the mechanisms associated with the disease remain poorly understood. This review highlights disruption of metabolism by antenatal high altitude hypoxia and the impact this has on pulmonary hypertension in the newborn with discussion of model organisms and human populations. There is particular emphasis on modifications in glucose and lipid metabolism along with alterations in mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 101 publications
(168 reference statements)
0
6
0
Order By: Relevance
“…These are also the essential mechanisms for developmental programming. Similar studies have emphasized that epigenetic modifications and programming in response to environmental stimuli are critical in achieving appropriate gene expression patterns, especially in specific lung tissues in relation to environmental signals [25,26]. This review focuses on aspects associated with chronic intrauterine hypoxia and epigenetic programming in bronchopulmonary dysplasia.…”
Section: Introductionmentioning
confidence: 91%
“…These are also the essential mechanisms for developmental programming. Similar studies have emphasized that epigenetic modifications and programming in response to environmental stimuli are critical in achieving appropriate gene expression patterns, especially in specific lung tissues in relation to environmental signals [25,26]. This review focuses on aspects associated with chronic intrauterine hypoxia and epigenetic programming in bronchopulmonary dysplasia.…”
Section: Introductionmentioning
confidence: 91%
“…In the heart, eNOS expression was increased at the protein and decreased at the gene expression level [ 85 ]. The effect of hypoxia on eNOS expression depends on the duration of hypoxia because increased ROS production may interfere with the bioavailability of NO during prolonged hypoxia [ 58 ]. The dynamic relationship between ROS and NO determines vascular tone because the hypoxia-induced increase in ROS, and thus the foetal ROS/NO ratio, potentiates peripheral vasoconstriction and redistribution of blood flow from the peripheral circulation to the vital organs, such as the brain and heart [ 112 ].…”
Section: Prenatal Hypoxiamentioning
confidence: 99%
“…Under normoxia, HIF-1α is rapidly degraded, but if the partial pressure of oxygen decreases, it is stabilized and accumulates in the cells. HIF-1α maintains oxygen homeostasis by regulating the expression of hundreds of genes and interacts with pathways involved in the regulation of the cardiovascular system, such as the chemoreflex, sympathetic drive [ 54 ], renin-angiotensin-aldosterone system (RAAS) [ 55 , 56 ], and local vessel wall components such as nitric oxide (NO) [ 57 , 58 , 59 ] and endothelin-1 [ 60 , 61 ]. Moreover, HIF directly interacts with the circadian clock because HIF-1α controls the expression of several canonical circadian genes and the response to hypoxia is gated by the circadian clock [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though normal pulmonary development occurs in the uterus in a relatively hypoxic environment, compression in the fetal CDH lungs by the abdominal content could decrease the lung perfusion, causing a drop in the nutrients and oxygen delivery. Previous studies demonstrated that excessive prenatal lung hypoxia has significant and lasting effects on the pulmonary vasculature, structurally and functionally [ 34 , 35 , 36 ]. On the other hand, cells undergo anaerobic metabolism under hypoxia [ 37 ], putting them at risk of energetic failure if unable to produce enough ATP for cellular functions [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%